Pola Asuh Positif Berhubungan dengan Perkembangan Anak Balita di Dusun Gintungan Desa Gogik: Positive Parenting Patterns Related to Toddler Development in Gintungan Hamlet, Gogik Village - Ernanda, Rika Yunita; Risma Aliviani Putri (Journal of Holistics and Health Sciences, 2025)
Parenting is an effort made by parents to guide, direct, teach and provide encouragement to children. Parental care greatly contributes to child development. One of the causes of delays or disruptions in children's development is the lack of active role of parents in supporting children's development. From the results of a preliminary study conducted in Gintungan hamlet, it was found that 4 out of 10 toddlers were left behind at work by their parents and entrusted to their grandmothers every day with the child's development according to their age, 2 out of 10 toddlers were not allowed to play outside the house except Saturdays and Sundays with the toddler's development they are still not clear in speaking and cannot make straight lines, 2 toddlers are still not clear in speaking a few sentences while they are already 36 months old and 2 toddlers out of 10 toddlers are cared for directly by their parents and can speak according to their age and can walk without a handrail.To determine the relationship between parenting patterns and the development of children under five in Gintungan Des Gogik Hamlet. This research uses a Correlation Analytical design using a cross sectional approach. The population in this study was 126 toddlers with a total sample of 56 parents and toddlers aged 12-60 months (1-5 years) at the posyandu in Gintungan hamlet. The sampling technique was qauta sampling. Data collection tools in this study used parenting style questionnaires and KPSP, data analysis tests used the chi-square test with p<a 0.05. From the research results, it was found that the p value was (0.041) < a (0.05), with the univariate test results mostly positive parenting patterns (66.1%) and appropriate development, namely (97.3%), and the test results Bivariately, it was found that the relationship between parenting styles and the development of children under five was p value (0.041), so Ha was accepted and Ho was rejected. This means that there is a relationship between parenting styles and the development of children under five. Parenting patterns are related to the development of children under five in Gintungan Hamlet, Gogik Village. It is hoped that parents will consider the parenting styles applied to their children more so that toddler development is optimal.   ABSTRAK  Pola asuh merupakan usaha yang dilakukan orang tua dalam membimbing, mengarahkan, mengajarkan serta memberikan dorongan kepada anak. Pengasuhan orang tua sangat berkontribusi dalam kaitannya dengan perkembangan anak. Keterlambatan atau gangguan perkembangan anak salah satu penyebabnya adalah peran aktif dari orangtua yang kurang dalam mendukung perkembangan anak. Dari hasil studi pendahuluan yang dilakukan di dusun Gintungan didapatkan 4 dari 10 balita ditinggal kerja oleh orang tuanya dan dititip kan ke  neneknya sehari-hari dengan perkembangan anak sesuai dengan usianya,  2 dari 10 balita tidak diperbolehkan main diluar rumah kecuali hari sabtu minggu dengan perkembangan balita masih kurang jelas dalam bicara dan belum bisa membuat garis lurus,  2 balita masih kurang jelas dalam bicara beberapa kalimat sementra usianya sudah 36 bulan dan 2 balita dari 10 balita diasuh lansung oleh orang tuanya dan sudah bisa berbicara sesuai umurnya dan bisa berjalan tanpa pegangan.Untuk mengetahui hubungan pola asuh orang tua terhadap perkembangan anak balita di Dusun Gintungan Des Gogik.Penelitian ini menggunakan desain Analitik Korelasi yang menggunakan pendekatan cross sectional. Populasi dalam penelitian ini 126 balita dengan jumlah sampel 56 orang tua dan balita yang berusia 12-60 bulan (1-5 tahun) di posyandu dusun gintungan. Teknik pengambilan sampel dengan qauta sampling, Alat pengumpulan data dalam penelitian ini menggunakan kuesioner pola asuh dan KPSP, uji analisa data menggunakan uji chi-square  dengan p< a 0.  Dari hasil penelitian didapatkan hasil nilai p value (0,041) < a (0,05) dengan hasil uji univariat sebagian besar berpola asuh positif (66,1%) dan perkembangan yang sesuai yaitu (97,3%), dan hasil uji Bivariat didapatkan hubungan pola asuh dengan perkembangan anak balita yaitu p value (0,041) maka Ha diterima dan Ho ditolak. Artinya terdapat hubungan antara pola asuh orang tua terhadap perkembangan anak balita. Pola asuh orang tua berhubungan terhadap perkembangan anak balita di Dusun Gintungan Desa Gogik.Diharapkan orang tua lebih mempertimbangkan pola asuh yang diterapkan pada anak agar perkembangan balita optimal.